LIAISON OF DESTRUCTIVE MENTAL STATES OF THE SOCIAL-PSYCHOLOGICAL SERVICE WORKERS IN THE PENITENTIARY INSTITUTIONS COMBINED WITH BOTH PROFESSIONAL BURNOUT AND PROFESSIONAL DEFORMATION - Chychuha, Maryna (PSYCHOLOGICAL JOURNAL, 2018)
The liaison of destructive mental states of the social-psychological service workers of penitentiary institutions combined with both professional burnout and professional deformation has been analyzed here in. It is noted that the results of the empirical research indicate the low level of situational anxiety, the middle and elevated level of personal anxiety, intenseness and phobia of the social-psychological service workers in the penitentiary institutions. The middle level of professional burnout among respondents, as well as the beginner level of the workers professional deformation with less than 5 years’ experience in the penitentiary institutions, and the middle level of the workers with more than 5 years’ experience has been researched. The correlations links of situational and personal anxiety and intenseness combined with the social-psychological service workers professional burnout have been revealed. Thus, respondents who work in institutions less than 1 year found reverse correlation between their personal anxiety and depersonalization - a component of professional burnout, which indicates that with increasing personal anxiety, the negative and cynical attitude of young professionals towards work and convicts is reduced, and vice versa. It is noted that such a correlation may indicate the indifference of employees to their work and its result. Direct correlative links between the personal anxiety and depersonalization of persons who work in the penitentiary institutions for more than 5 years has been founded. It means that with increase of personal anxiety the level of cynicism in regard to convicts and negative attitude towards own work will also increase. The correlative links of the personal anxiety and reduction of the personal achievement has been found in all investigated groups of respondents which means the higher anxiety level, all the more negatively the workers evaluate their own professional achievements as well as themselves, feel their incompetence in professional field, and vice versa. Direct correlative links of the situational anxiety and achievements’ reduction of the workers with less than 3 years’ experience of work in penitentiary institutions has been researched. It means the higher anxiety level, all the more negatively the young workers evaluate their own professional achievements, feel their incompetence in professional field in specific situations of their professional activity. Direct correlative links between the intenseness and reduction of personal achievements of those who work less than 3 years has been found, i.e. the workers cannot properly evaluate their professional achievements being under stress. Direct correlative links between the situational anxiety and professional deformation of the penitentiary institutions workers with more than 3 years’ experience has been established. It was specified that in accordance to the revealed links at the anxiety level increasing the level of professional deformation has been noticed too.